Hubungan Perilaku Caring Dan Implementasi Keselamatan Pasien Dengan Kepuasan Pasien Di Ruangan Rawat Inap - Raynaldi , Muhammad; Amal, Andi adriana; Ilhamsyah, Ilhamsyah; Hidayah, Nur; Rasywan, Muh (Alauddin Scientific Journal of Nursing, 2024)
Introduction: Patient satisfaction is one of the goals of improving healthcare service quality. The level of patient satisfaction in 2020 in several provinces in Indonesia showed a satisfaction rate of 42.8% in Central Maluku and 44.4% in West Sumatra, with 58.6% overall. This indicates that patient satisfaction still needs to be improved. One factor contributing to low patient satisfaction is the implementation of patient safety, and the caring behavior of nurses is crucial in meeting patient satisfaction. Low service quality can lead to patient dissatisfaction and various complaints.Objective: This study aims to determine the relationship between caring behavior and the implementation of patient safety with patient satisfaction in inpatient wards. Methods: This research is a quantitative study using a cross-sectional approach, with sampling techniques employing proportional random sampling, resulting in a sample size of 162 individuals. Data collection for each variable was conducted using a questionnaire.Results: Based on statistical tests using the Fisher exact test, a p-value of 0.001 (p<0.05) was obtained, indicating a relationship between caring behavior and patient satisfaction. Additionally, the Fisher exact test yielded a p-value of 0.004 (p<0.05), suggesting a relationship between the implementation of patient safety and patient satisfaction.Conclusion: There is a relationship between caring behavior and the implementation of patient safety with patient satisfaction in inpatient wards.